2016
DOI: 10.1038/srep27878
|View full text |Cite
|
Sign up to set email alerts
|

Aldh1 Expression and Activity Increase During Tumor Evolution in Sarcoma Cancer Stem Cell Populations

Abstract: Tumors evolve from initial tumorigenic events into increasingly aggressive behaviors in a process usually driven by subpopulations of cancer stem cells (CSCs). Mesenchymal stromal/stem cells (MSCs) may act as the cell-of-origin for sarcomas, and CSCs that present MSC features have been identified in sarcomas due to their ability to grow as self-renewed floating spheres (tumorspheres). Accordingly, we previously developed sarcoma models using human MSCs transformed with relevant oncogenic events. To study the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 58 publications
(101 reference statements)
3
41
1
Order By: Relevance
“…Considering that T-CDS17 displayed increased aggressiveness (higher invasion and tumor formation ability) than CDS-17 cells [45], the increase in SORE6+ cells could respond to an increase of the CSC burden during tumor progression and adaptation to new microenvironments. Similar findings regarding the gain of aggressiveness upon in vivo tumor growth associated to an increase of CSC markers, such as ALDH activity or OCT4 expression, have also been described in different types of sarcoma [22,35,45,46]. These findings support that serial transplantation could represent an efficient way of enriching/selecting CSC subpopulations [18].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Considering that T-CDS17 displayed increased aggressiveness (higher invasion and tumor formation ability) than CDS-17 cells [45], the increase in SORE6+ cells could respond to an increase of the CSC burden during tumor progression and adaptation to new microenvironments. Similar findings regarding the gain of aggressiveness upon in vivo tumor growth associated to an increase of CSC markers, such as ALDH activity or OCT4 expression, have also been described in different types of sarcoma [22,35,45,46]. These findings support that serial transplantation could represent an efficient way of enriching/selecting CSC subpopulations [18].…”
Section: Discussionsupporting
confidence: 80%
“…We found that self-renewed tumorspheres formed by these cells showed increased expression of several CSC-related genes, including SOX2. Furthermore, by comparing the tumorigenic properties of these models with those of their xenograft-derived cell lines, we found that SOX2 expression was progressively enhanced in CSC-enriched tumorspheres during sarcoma progression toward more aggressive phenotypes, hence highlighting its potential applicability as CSC marker in sarcomas [35]. To further and significantly extend these data, herein we introduced a reporter system to monitor the transcriptional activity due to SOX2 and/or OCT4 (SORE6) [29] in a model of undifferentiated pleomorphic sarcoma (UPS) and chondrosarcoma patient-derived cell lines thus analyzing for the first time the ability of isolated SOX2/OCT4-positive cells as tumor-promoting CSCs in sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we tested the ability of these indolocarbazole analogs to target cancer stem cell (CSC)‐enriched tumorsphere cultures of MSC‐5H‐FC and T‐5H‐FC#1 cells . Again, EC‐70124 was more efficient than midostaurin in eliminating CSCs (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tumorsphere formation protocol and the analysis of the effects of drugs on tumorsphere cultures were previously described …”
Section: Methodsmentioning
confidence: 99%
“…of tumor stem cells; Oct4 abnormal expression is associated with self-renewal and unrestricted proliferative function of tumor stem cells, as well as epithelial-mesenchymal transition phenotype[47][48][49][50][51] ; ALDH1 abnormal expression enhances the cytotoxic effects of tolerant drugs of stem cells and tumor stem cells, as well as other compounds, contributing to and maintaining multidrug resistance of tumor stem cells and cell anoikis resistance[52][53][54][55] . Western blot analysis showed that the supernatants of 1-2F monoclonal cells with different dilution ratios reduced the expression levels of CD44, ABCG2, Bmi1, Nanog, Oct4 and ALDH1 proteins of HUSSLCs in concentrationdependent manner (P < 0.05).…”
mentioning
confidence: 99%